UNCERTAINTY REDUCTION PADA MAHASISWA TAHUN PERTAMA DI MASA PANDEMI COVID-19 - Ascharisa Mettasatya Afrilia; Anisa Setya Arifina; Ari Rahman; Eka Widyawati (SOURCE : Jurnal Ilmu Komunikasi, 2022)
This research aims to reveal the forms of uncertainty experienced by first-year students during the pandemic as well as to describe the uncertainty reduction strategies that have been carried out. The method used is a qualitative research method with a case study approach. Data analysis was carried out by selecting and sorting data, both primary and secondary according to the focus of this research and tested for its validity level using triangulation of sources and methods. The results showed that the interaction process of first-year students during the pandemic took place more virtually. As a result, informants experience three forms of uncertainty at the same time, namely cognitive uncertainty, behavioral uncertainty, and relationship uncertainty. One of the things that creates uncertainty for first-year students during this pandemic is the concealment of faces and identities by not turning on the camera during virtual interactions. This then causes individual confusion in behaving to other individuals. The strategy taken to reduce this uncertainty is in the form of planning and seeking information, while hedging measures are not found in this research.